Optimization of Fermentation Time in Instant Tea Production - Sinija, V R; Mishra, H N; Bal, S (Journal of Agricultural Engineering, 2006)
Fermentation should be optimum for the production of good quality tea. One of the methods commonly followed today is based on the amount of theaflavin (TF) formed during fermentation. For this, samples (juice for instant tea (IT) and pressed leafresidue for black tea granules (TG)) were collected at specific interval of time during fermentation and the optical density values were determined by a spectrophotometer. Optimum period was indicated by the peak of the curve obtained by plotting optical density (00) values of the sample vs. fermentation time. The optimum fermentation time for IT was 1 h and for TG was 1.5 h. The amount of TF formed, as indicated by the increase in OD in juice increased with increase in fermentation time up to 60 min and after that it decreased. Similar trend was found for pressed leaf residue also where the OD increased up to 90 min. The decrease in theaflavin content beyond a certain time may be due to the conversion of theaflavin to thearubigins (TR). The result was emphasized by another experiment in which IT and TG were prepared with different fermentation times, and the prepared samples were analyzed for the quality by a sensory evaluation panel.